IMPROVED DISTRIBUTION TRANSFORMER SECURITY WITH HYBRID FUSE CUT OUT SYSTEM - Yogi Prayoga; Solly Aryza; Adi Sastra P Tarigan (INFOKUM, 2022)
This study aims to study the performance of the safety system used in distribution transformers that reduce the voltage from 20 kV to 230/400 V with a fuse cout out safety device. Where the problem that often arises in the field is a disturbance in the electrical energy distribution system which results in blackouts. The methods used in this research are field surveys which are compared with simulations in the laboratory of the electric power protection system, which aims to determine the performance of theaelectricapoweraprotectionisystem of fuse cut out in network security. Data is taken from cases that occurred at the ST 87 substation TP.02 ULP Stabat. Where the research results obtained are the magnitude of the fault current which is equal to the current rating of the installed fuse link. So that at the end of the study, several results were found where the amount of fault current had exceeded the existing transformer resistance limit, so that the transformer was damaged and disrupted the 20 kv network system.